THE EFFECTIVENESS OF THE ELECTRONIC MATCHING AND VERIFICATION APPLICATION (E-COKLIT) REGIONAL HEAD ELECTION 2024 (PILKADA) IN PALU CITY - Andi Maman Firmansyah; Sri Azizah; Rahmawati Hi. Nawir; Nurhannis (RADJA PUBLIKA, 2026)
The Effectiveness of the Electronic Matching and Verification Application (E-Coklit) Regional Head Election 2024 (Pilkada) in Palu City This study aims to examine the extent to which the Electronic Matching and Verification Application (E-Coklit) was effectively utilized during the 2024 Regional Head Election (Pilkada) in Layana Indah Subdistrict, Palu City. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. This study adopts Richard M. Steers’ (1985) theory of organizational effectiveness, which includes three indicators: goal attainment, integration, and adaptation. The findings indicate that the use of the E-Coklit application has not been fully effective in supporting voter data updating in the 2024 Pilkada within the Layana Indah area. This is primarily due to the suboptimal performance of two indicators, namely goal attainment and adaptation. Regarding the goal attainment indicator, although the E-Coklit application has accelerated the workflow of voter data updating officers (Pantarlih), their workload has increased due to technical issues and a lack of cooperation from some members of the community. Meanwhile, the integration indicator has functioned well, as demonstrated by effective hierarchical communication and coordination. However, in terms of adaptation, although Pantarlih officers have shown a good ability to adapt, the overall effectiveness is hindered by infrastructural constraints. These include limited application compatibility, unstable internet connectivity, and server errors or overloads. As a result, voter data verification must be conducted both manually and electronically at the same time, reducing overall efficiency.